Research and Implementation of SDK Simulation Platform for Chip Drivers - LI Wenyi; XU Zhisheng (Guangtongxin yanjiu)
【Objective】With the continuous advancement of Integrated Circuit (IC) design and manufacturing process, the design scale of System on Chip (SoC) has become increasingly larger, and the corresponding Software Development Kit (SDK) has also become more complex. Shortening the development time and rapid application of SDK is the key to the success of chip development.【Methods】In this paper, a chip SDK simulation platform is designed, which supports automatic extraction of chip logic design information. The software local image of extracted logic information based on the designed chip data structure is realized. The multi-threading of configuration, alarm and performance is developed to simulate the multi-task polling and network management reporting in the actual single-disk application. By connecting the SDK project to the serial port tool through the virtual serial port, the Shell command set provides interaction among developers and the SDK projects under the SDK simulation platform.【Results】The test results based on optical communication chip show that the SDK simulation platform can realize the functions of chip software level simulation, multi-thread debugging simulation and multi-function interaction under Shell command set.【Conclusion】The SDK simulation platform implemented in this paper can be applied to the early development and late application maintenance of chips. It has the functions of avoiding the development obstruction caused by the shortage of hardware resources, converging the difference of chip conversion, and providing a convenient SDK debugging method, which is of great significance to shorten the development time and accelerate the rapid application of chips.